The Faces of Contemporary Labour Market Segmentation - Bilczak, Wasyl; Bilczak, Michał (Olsztyn Economic Journal, 2018)
This article discusses the theoretical aspects of regional economic systems. Particular attention was paid to the nature of the development of border regions and coastal regions under new geopolitical circumstances. The special aspects of the functioning of those territorial units in the Russian Federation and the Commonwealth of Independent States (CIS) were illustrated. The author has highlighted the role of the border effect which is closely related to border infrastructure (border crossings, border inspection and customs posts, communication, service, and logistics) as well as the possibility of exploiting the potential resources (land, forest, water, and leisure) extensively on both sides of the border. Great emphasis was put on the forms of international cooperation between inhabitants of border regions, institutions and organisations.